Urban flood regulating ecosystem services under climate change: how can Nature-based Solutions contribute? - Wübbelmann, Thea; Förster, Kristian; Bouwer, Laurens M.; Dworczyk, Claudia; Bender, Steffen; Burkhard, Benjamin (Frontiers in Water, 2023)
Urban areas are mostly highly sealed spaces, which often leads to large proportions of surface runoff. At the same time, heavy rainfall events are projected to increase in frequency and intensity with anthropogenic climate change. Consequently, higher risks and damages from pluvial flooding are expected. The analysis of Flood Regulating Ecosystem Services (FRES) can help to determine the benefits from nature to people by reducing surface runoff and runoff peaks. However, urban FRES are rarely studied for heavy rainfall events under changing climate conditions. Therefore, we first estimate the functionality of current urban FRES-supply and demand under changing climate conditions. Second, we identify the effects of Nature-based Solutions (NbS) on FRES-supply and demand and their potential future functionality and benefits concerning more intensive rainfall events. A district of the city of Rostock in northeastern Germany serves as the case study area. In addition to the reference conditions based on the current land use, we investigate two potential NbS: (1) increasing the number of trees; and (2) unsealing and soil improvement. Both NbS and a combination of both are applied for three heavy rainfall scenarios. In addition to a reference scenario, two future scenarios were developed to investigate the FRES functionality, based on 21 and 28% more intense rainfall. While the potential FRES-demand was held constant, we assessed the FRES-supply and actual demand for all scenario combinations, using the hydrological model LEAFlood. The comparison between the actual demand and supply indicates the changes in FRES-supply surplus and unmet demand increase. Existing land use structures reached a FRES capacity and cannot buffer more intense rainfall events. Whereas, the NbS serve FRES benefits by increasing the supply and reducing the actual demand. Using FRES indicators, based on hydrological models to estimate future functionality under changing climate conditions and the benefits of NbS, can serve as an analysis and decision-support tool for decision-makers to reduce future urban flood risk.